Efficient protection of witnesses and victims:: Strategies to confront organised crime in Paraguay (Legal journal - Research in Legal and Social Sciences, 2020)
Paraguay is focus of attention in Latin America, when it comes to reports on organised crime -specially with respect to drug trafficking-, that place the country constantly in the worst positions on the ranking lists of fight against organised crime. This research is focused on the analysis of the protection of witnesses and victims in Paraguay, given the fact that by Act number 4083 of 2011, the “Witness and  Victims  Accompanying  and  Protection  Programme”  was  created,  under  the  authority of the Attorney's General Office. The study covers the concept of organised crime and its scope, the delimitation of the concepts of victims and witnesses, the identification of national and international instruments that support their protection and that are enforceable to judicial processes. The study concludes with an analysis of  the  implementation  of  these  instruments  in  the  mentioned  processes,  by  the  Public Ministry. The overall result of the analysis is, that the protection suffers from wicknesses that violate fundamental rights, such as life and integrity, especially in cases of organised crime, what makes the programme ineffective. The identified wicknesses are: the impossibility to change or protect the identity in severe cases; long  distance  testimonies  from  witnesses,  or  testimonies  by  technical  procedures  that distort the voice or image to avoid eye contact with the defendant during the hearing, in order to ensure the incriminating testimony's effectiveness.
Keywords: Witnesses; Victims; security measures; criminal process; assistance